Production of transgenic tobacco plants expressing GS1 gene for the increase ofnitrogen use efficiency - Gấm, Nguyễn Thị Hồng; Giang, Trần Thị Hương; Thảo, Bùi Phương; Đoài, Nguyễn Văn; Thơm, Nguyễn Thị; Thắng, Bùi Văn; Ngọc, Phạm Bích; Hà, Chu Hoàng (Vietnam Journal of Biotechnology, 2016)
Glutamine synthetase (GS, CE 6.3.1.2) is an enzyme that catalyzes the ATP-dependent condensation of glutamic acid with ammonia to yield glutamine. Glutamine synthetase is a key enzyme involved in the assimilation of inorganic nitrogen into organic forms. In plant cells, GS is present in both chloroplasts (GS2) and cytoplasm (GS1), in which GS1 can assimilate nitrogen source. In this study, one transgenic vector pBI121 carrying GS1 gene under the control of promoter 35S (pBI121::GS1) were successfully constructed. This vector containing G1S gene was transformed into tobacco leaves pieces via Agrobacterium tumefaciens strain C58. Five weeks after cultivation, there were 28 tobacco lines which had roots on the medium added kanamycin 50 mg/l. Then, the presence of G1S gene in these tobacco lines was tested from leaves in the next experiments. PCR and Southern blot confirmed that there are five tobacco lines carrying transferred GS1 gene. The effectiveness of nitrogen using in GS1 transgenic tobacco plants in vitro was evaluated. The tissue fresh weight, number and height of shoots forming buds and rooting ability of GS1 transgenic tobacco plants were greater than those of non-GM plants in the medium of low nitrogen concentration (0.1X - 0.2X). Assessment of crop growing in a greenhouse demonstrated that GS1 transgenic tobacco plants grow faster than non-transgenic ones. In detail, the increment of plant height after planting 03 months and 05 months in greenhouse is 43.55% and 33.29%, respectively. These results provide a scientific basis for the development of other genetically modified plants which enhanced nitrogen-use efficiency